SKSR1 identified as key virulence factor in Cryptosporidium by genetic crossing - Wei He; Lianbei Sun; Tianyi Hou; Zuwei Yang; Fuxian Yang; Shengchen Zhang; Tianpeng Wang; Xinran Wang; Na Li; Yaqiong Guo; L. David Sibley; Yaoyu Feng; et al. (Nature Communications)
Abstract Cryptosporidium is a major cause of severe diarrhea. Although Cryptosporidium isolates exhibit significant differences in infectivity and virulence, the genetic determinants for these traits are not clear. In this study, we use classical genetics to cross two Cryptosporidium parvum isolates of different virulence and use bulk segregant analysis of whole-genome sequences from the progeny to identify quantitative trait loci (QTL) associated with Cryptosporidium infectivity and virulence. Of the 23 genes in three QTL, two have loss-of-function mutations in the low-virulence isolates, including the SKSR1 gene encoding a variant secretory protein. Deletion of the SKSR1 gene or expression of the frame-shifted sequence reduces the pathogenicity of the virulent isolate. SKSR1 is expressed in small granules and secreted into the parasite-host interface during invasion. These results demonstrate that SKSR1 is an important virulence factor in Cryptosporidium, and suggest that the extended SKSR protein family, encoded by clusters of subtelomeric genes, may contribute to pathogenesis.